REALITAS MATERIALITAS AUDIT DALAM TEORI DAN PRAKTIK - Senny Harindahyani (Jurnal Akuntansi Bisnis, 2017)
This Interpretive Intractionism Research objectice is to reveal the implementation of materialiality concept from the auditor’s point of view. Auditor decision in setting materiality is one of the important step in audit process, because it concerns with acceptable risk level of material misstatement. Documentation of materiality which has been set in Standar Profesional Akuntan Publik (SPAP) is a mandatory provision, both in praxis and from the theoretical point of view. Therefore, proper documentation upon materiality is necessary to support the professional judgment and avoid the thinking of negligence of audit standard. Without proper audit documentation, the auditor professionalism will be in question, especially when considering the Utilitarian Perspective. There are many reasons to justify in lowering costs & time budget upon audit process. This circumstances force the auditor (audit partner) to decide the audit materiality only by instinct and verbally communicated to the audit team members. To maintain the professionalism and enhancing public level of confidence, this issue must be addressed accordingly.     Keywords: Materiality, Auditor, Audit Documentation.